Multifaceted intervention to improve obstetric practices: The OPERA cluster-randomized controlled trial. (August 2017) - Dupont, Corinne; Winer, Norbert; Rabilloud, Muriel; Touzet, Sandrine; Branger, Bernard; Lansac, Jacques; Gaucher, Laurent; Duclos, Antoine; Huissoud, Cyril; Boutitie, Florent; Rudigoz, René-Charles; Colin, Cyrille; et al.
Abstract: Objective: Suboptimal care contributes to perinatal morbidity and mortality. We investigated the effects of a multifaceted program designed to improve obstetric practices and outcomes. Study design: A cluster-randomized trial was conducted from October 2008 to November 2010 in 95 French maternity units randomized either to receive an information intervention about published guidelines or left to apply them freely. The intervention combined an outreach visit with a morbidity/mortality conference (MMC) to review perinatal morbidity/mortality cases. Within the intervention group, the units were randomized to have MMCs with or without clinical psychologists. The primary outcome was the rate of suboptimal care among perinatal morbidity/mortality cases. The secondary outcomes included the rate of suboptimal care among cases of morbidity, the rate of suboptimal care among cases of mortality, the rate of avoidable morbidity and/or mortality cases, and the incidence of, morbidity and/or mortality. A mixed logistic regression model with random intercept was used to quantify the effect of the intervention on the main outcome. Results: The study reviewed 2459 cases of morbidity or mortality among 165, 353 births. The rate of suboptimal care among morbidity plus mortality cases was not significantly lower in the intervention than in the control group (8.1% vs. 10.6%, OR [95% CI]: 0.75 [0.50-1.12], p = 0.15. However, the cases of suboptimal care among morbidity cases were significantly lower in the intervention group (7.6% vs. 11.5%, 0.62 [0.40-0.94], p = 0.02); the incidence of perinatal morbidity was also lower (7.0 vs. 8.1‰, p = 0.01). No differences were found between psychologist-backed and the other units. Conclusions: The intervention reduced the rate of suboptimal care mainly in morbidity cases and the incidence of morbidity but did not succeed in improving morbidity plus mortality combined. More clear-cut results regarding mortality require a longer study period and the inclusion of structures that intervene before and after the delivery room. (ClinicalTrials.gov ID: NCT02584166)